Head Teachers’ Instructional Supervisory Practices and Teachers’ Motivation in Teaching - Mushtaq Ahmed, Fareeha Samee, Shaista Khalid (PJE, 2023)
The study determined the relationship between Government Secondary school head teachers’ instructional supervisory practices and teachers’ motivation in teaching. The study was correlational and survey technique was used for data collection. The population of the study was all the male and female head teachers and teachers working in the Government Secondary schools of District Sargodha.